2015
DOI: 10.1111/cogs.12269
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Model of Linguistic Humor in Puns

Abstract: Humor plays an essential role in human interactions. Precisely what makes something funny, however, remains elusive. While research on natural language understanding has made significant advancements in recent years, there has been little direct integration of humor research with computational models of language understanding. In this paper, we propose two information‐theoretic measures—ambiguity and distinctiveness—derived from a simple model of sentence processing. We test these measures on a set of puns and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 45 publications
0
47
1
1
Order By: Relevance
“…Since the earliest times, it has performed an essential role in human interaction (Kao, Levy & Goodman, 2015). In addition, human beings are the only species that laughs (Ashipaoloye, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the earliest times, it has performed an essential role in human interaction (Kao, Levy & Goodman, 2015). In addition, human beings are the only species that laughs (Ashipaoloye, 2013).…”
mentioning
confidence: 99%
“…The field of the linguistics of humor is in many ways still in its infancy (Attardo, 2014). For the past five years, linguistic humor research in language has shed light on humorous discourse, for instance, dialogues of the American TV series The Big Bang Theory (Ma & Jiang, 2013), Indonesian stand-up comedy (Afidah & Wahyudi, 2014), Romanian parliamentary discourse by a controversial political figure of Romanian politics, Corneliu Vadim Tudor (Săftoiu & Popescu, 2014), Obama's most memorable speeches (Kayam, 2014), a computational model of linguistics humor in puns (Kao et al, 2015), Dudley's political cartoons (Mwetulundila & Kangira, 2015), English advertisements in India (Chetia, 2015), persuasion in Jesus Christ's Humor (Al-Ameedi & Abdulmajeed, 2016), and controversial humor (Hietalahti, 2016).…”
mentioning
confidence: 99%
“…Each word also has a latent meaning assignment variable f controlling whether it is generated from an unconditional unigram language model or a unigram model conditioned on z. Ambiguity is defined as the entropy of the posterior distribution over z given all the words, and distinctiveness is defined as the symmetrized KL-divergence between distributions of the assignment variables given the pun meaning and the alternative meaning respectively. The generative model relies on p(x i | z), which Kao et al (2015) estimates using human ratings of word relatedness. We instead use the skip-gram model described in Section 3.3 as we are interested in a fully-automated system.…”
Section: Analysis Of the Surprisal Principlementioning
confidence: 99%
“…Recently, Yu et al (2018) proposed an unsupervised approach that generates puns from a neural language model by jointly decoding conditioned on both the pun and the alternative words, thus injecting ambiguity to the output sentence. However, Kao et al (2015) showed that ambiguity alone is insufficient to bring humor; the two mean-ings must also be supported by distinct sets of words in the sentence.…”
Section: Introductionmentioning
confidence: 99%
“…Most computational treatments of puns to date have focused on generative algorithms Ritchie, 1994, 1997;Ritchie, 2005;Hong and Ong, 2009;Waller et al, 2009;Kawahara, 2010) or modelling their phonological properties (Hempelmann, 2003a,b). However, several studies have explored the detection and interpretation of puns (Yokogawa, 2002;Taylor and Mazlack, 2004;Miller and Gurevych, 2015;Kao et al, 2015;Miller and Turković, 2016;Miller, 2016); the most recent of these focus squarely on computational semantics. In this paper, we present the first organized public evaluation for the computational processing of puns.…”
Section: Introductionmentioning
confidence: 99%